2016
DOI: 10.1007/s00360-016-1032-y
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes of cholinergic response in the atrium of Arctic navaga cod (Eleginus navaga)

Abstract: Fishes of north-temperate latitudes exhibit marked seasonal changes in electrical excitability of the heart partly as an outcome of temperature-dependent changes in the density of major K ion currents: delayed rectifiers (I, I) and background inward rectifier (I). In the arctic teleost, navaga cod (Eleginus navaga), I and I are strongly up-regulated in winter. The current study tests the hypothesis that the ligand-gated K current, the acetylcholine-activated inward rectifier, I, is also modified by seasonal ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…The favorable I Na :I K1 ratio (large safety factor) makes the atrial myocytes easily excitable and protects them against heat-dependent deterioration of excitability. It is noteworthy that EE of atrial myocytes can be depressed by inducing an outward K + current by acetylcholine (I KAch ) (Abramochkin and Vornanen, 2017). However, the temperature-induced increase in I KAch is not large enough to prevent atrial excitability in vivo, as shown by the persistence of P waves in the ECG (Fig.…”
Section: Musclementioning
confidence: 99%
“…The favorable I Na :I K1 ratio (large safety factor) makes the atrial myocytes easily excitable and protects them against heat-dependent deterioration of excitability. It is noteworthy that EE of atrial myocytes can be depressed by inducing an outward K + current by acetylcholine (I KAch ) (Abramochkin and Vornanen, 2017). However, the temperature-induced increase in I KAch is not large enough to prevent atrial excitability in vivo, as shown by the persistence of P waves in the ECG (Fig.…”
Section: Musclementioning
confidence: 99%
“…Thus, it appears that unlike more northern temperate species ( Haverinen and Vornanen, 2020 ; Badr et al., 2018 ), excitability due to resting membrane potential in the ventricle of this polar fish is resistant to both temperature and a key petroleum pollutant. In vivo, the resting membrane potential of navaga atrial myocytes is maintained, at least in part, through vagal tone which activates the ACh-dependent inward rectifier I KACh ( Abramochkin and Vornanen, 2017 ). Once the atrial myocytes are isolated and lose this tone, they depolarise as the density of their inward rectifier current I K1 is very small ( Abramochkin and Vornanen, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The bulbus arteriosus was cannulated and myocytes were isolated by retrograde perfusion of the heart with isolation solution [(mmol L −1 ): NaCl 100, KCl 10, KH 2 PO 4 ∙2H 2 O 1.2, MgSO 4 ∙7H 2 O 4, taurine 50, glucose 10 and HEPES 10 at pH of 6.9], containing proteolytic enzymes. The concentration of enzymes (collagenase type IA, 0.5 mg ml −1 ; trypsin type IX, 0.33 mg ml −1 ; fatty acid free bovine serum albumin, 0.33 mg ml −1 ) were selected in accordance with earlier studies on navaga ( Abramochkin and Vornanen, 2017 , 2015 ). Isolated atrial and ventricular myocytes were obtained by mincing and triturating of ventricular and atrial myocardium after 10–12 min of heart perfusion.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations